2019
DOI: 10.2478/rtuect-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Emission Decrease Possibility from Household Sector using Flue Gas Condenser – Fog Unit. Analysis and Interpretation of Results

Abstract: Particulate matter (PM) is a significant pollution problem on the global scale. There are different ways to measure PM from stationary sources. The most used types of PM collection methods include different filters. These include cellulose, glass, mixed and membrane filters. In this study PM samples were measured in the flue gas condenserfog unit system before and after the unit according to ISO 9096 standard using isokinetic and gravimetric method. PM concentrations after fog unit were measured at different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Results show that it is possible to obtain particulate matter reduction from 70 % to 77.3 % with each nozzle type, if water flowrate is 150 l/h and higher. A more detailed study about particulate matter reduction with the fog unit technology can be found in another paper done by Priedniece et al [31]. Water spraying in the fog unit was organized by using circulation water pump.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results show that it is possible to obtain particulate matter reduction from 70 % to 77.3 % with each nozzle type, if water flowrate is 150 l/h and higher. A more detailed study about particulate matter reduction with the fog unit technology can be found in another paper done by Priedniece et al [31]. Water spraying in the fog unit was organized by using circulation water pump.…”
Section: Resultsmentioning
confidence: 99%
“…The energy efficiency of provided technology was selected as the main criteria in this case. However, in another study about the same technology, it will be possible to find results, where the main focus was put on particulate matter decrease possibilities using the fog unit [31].…”
mentioning
confidence: 99%
“…The efficiency of the fog unit reached in experiments is up to 15.39 % (capacity 3.11 kW for pellet boiler with capacity 20 kW) and the operating principle of the unit system is described in more detail in a paper by Priedniece et al [6]. The use of a fog unit significantly decreases particulate matter amount in flue gases from combustion units, as shown by results described in [7], where PM reduction efficiency is from 28.6 % to 77.3 %, depending on used nozzle type, sprayed water flowrate and other parameters. Integrating this device in households would lead to essential benefits both locally and globally, creating not only positive impact on the environment, but also on human health.…”
Section: Introductionmentioning
confidence: 83%
“…Finally, findings in [41] support a unidirectional causality from GDP to energy consumption. The abovementioned works provided a good foundation for more focused studies on other aspects of the relationship between economic growth, energy consumption, and carbon dioxide emissions presented in [42]- [46].…”
Section: Related Studiesmentioning
confidence: 99%